“COMPARATIVE ANALYSIS OF BILINGUAL AND MONOLINGUAL DICTIONARIES” - Ruzamatova La’lixon Ravshan qizi (American Journals, 2023)
The first type of dictionary that is discussed when theory is applied to dictionaries is the monolingual variety. However, there is no justification to believe that bilingual dictionaries are significantly less susceptible to theory than their monolingual equivalents. Word meaning is the area of linguistics that has the most relevance for lexicography. The collection of things a word can refer to, the lexical relationships a word has with other words, how a word has been used, or the semantic information associated with a word that is stored in a speaker's brain have all been proposed as ways to define word meaning.
Keywords: theory, monolingual dictionary, justification, susceptible, lexicography.